Do males really prefer non-fiction, and why does it matter? - Merga, Margaret (AATE, 2017)
© 2017, AATE - Australian Association Teaching English. All rights reserved. International findings indicate that there is a gap in the literacy performance of schoolaged males and females, which has led to a focus on how to address this issue. Research suggests that an individual’s literacy outcomes can be improved by regular recreational book reading, and therefore increasing frequency of engagement in this practice is seen as beneficial. However, the strategies and solutions employed to foster greater engagement in reading tend to subscribe to a problematic theoretical root. Essentialist conceptions of gender often frame educational and policy responses to this gender gap. Amongst other notions, males have been constructed as uniformly preferring non-fiction. This paper draws on previously unpublished data from the 2015 International Study of Avid Book Readers and the 2016 Western Australian Study in Children’s Book Reading to examine the reading preferences of males. Male respondents in both studies displayed no marked preference for non-fiction, and males were more likely to prefer to exclusively read fiction than non-fiction. As essentialism requires homogeneity due to its biological basis, this paper ultimately challenges the legitimacy of using an essentialist framework to generate knowledge about how to best encourage males to read, exploring the risks inherent in this practice.